Maternal body mass index in early pregnancy and offspring mortality up to early adulthood: A nationwide cohort study - Hui Wang; Hua Chen; Jette Möller; Yajun Liang; Krisztina D. László (PLOS Medicine, 2026)
Background Obesity is increasingly common among women of childbearing age worldwide. Maternal obesity during pregnancy may have long-term implications for offspring health, but its association with offspring mortality remains not well understood. In this nationwide cohort study, we examined the associations of maternal body mass index (BMI) in early pregnancy with all-cause and cause-specific mortality in offspring. Methods and findings We included 2,606,684 live births in Sweden during 1982–2014 (except for 1990 and 1991) and followed them from birth until death, emigration from Sweden, or December 31, 2023, whichever came first. Information on maternal BMI during early pregnancy was obtained from the Medical Birth Register and was categorized as: underweight (BMI